Who does what in enabling ambidexterity? Individual Actions and HRM practices. Issue 4 (21st February 2019) - Swart, Juani; Turner, Neil; van Rossenberg, Yvonne; Kinnie, Nicholas
Abstract: In this paper, we explain how ambidexterity, the simultaneous pursuit of exploration and exploitation, is enabled at the individual level of analysis. Research on ambidexterity has been dominated by theoretical approaches focusing on the organisational level; however, we know little about how ambidexterity is enacted by employees. There is also limited work on the multilevel aspects of individual employee actions, for example, particular roles and specifically the level of seniority of the role. We address these gaps by asking: Which individual actions are undertaken by employees at particular levels of seniority in the organization to enable ambidexterity ? In order to answer this question we draw on previous research to construct reliable measures of the individual actions that enable ambidexterity. The hypothesized mediation effect of these individual actions is confirmed on the basis of survey data from 212 employees from a UK-based Professional Service Firm. The findings indicate that senior employees are more likely to use 'integration', 'role expansion' and 'tone setting', whilst employees with specialist knowledge about their clients use 'gap filling' to enable ambidexterity. Finally, we draw together these findings with 35 interviews conducted to present the HRM practices which support ambidexterity.